Renal Papillary Necrosis as the First Presenting Clinical Feature in a Sickle Beta and Thalassemic Child - Kumar, Jagadish; Chowdary, Satyesh; VG, Manjunath; Das, Sudha Kiran; Vuyyuru, Manovihari (Journal of Nepal Paediatric Society, 2020)
In sickle cell disease (SCD), the clinical manifestations are due to episodes of vascular occlusion and haemolysis. Most of the children experience vaso-occlusive pain episodes by the age of six years. Renal injury in sickle cell disease referred to as sickle cell nephropathy is a frequent yet under-recognised complication. Renal papillary necrosis (RPN) as the first presentation in SCD is rare. We are reporting a 12 year old child with no prior vaso-occlusive episodes, presenting with renal papillary necrosis due to Sickle Beta and Thalassemia.